Kvantno računalništvo - Caf, Enej (Matrika, 2021)
The article introduces theoretical principles in quantum computing and gives insight into five existing realisations of qubits. In the introduction historical background of quantum computing is presented, followed by the description of qubits, superposition and entanglement. Furthermore, elementary quantum gates and universal sets of gates are discussed. In addition, DiVincenzo criteria, decoherence and quantum error correction are presented. In the end, five types of promising physical systems used in existing qubits are pointed out: nuclear magnetic resonance, trapped ions, superconducting quantum interference device, quantum dots and linear optical quantum computer.
Keywords: kubiti; kvantna mehanika; kvantna prepletenost; kvantna vrata; kvantno računalništvo; quantum computing; quantum entanglement; quantum gates; quatnum mechanics; qubits